Delayed Hypersensitivity Reactions Provoked by Ribosomes from Acid-Fast Bacilli: Physical Characteristics and Immunological Aspects of Core Ribosomal Proteins from Mycobacterium smegmatis - Loge, R. V. (1974)
Ribosomal subunits from Mycobacterium smegmatis were analyzed by using sedimentation velocity, sedimentation equilibrium, and acrylamide gel electrophoresis experiments. These s(2̊0.w) values for the subunits are 48.7S and 28.1S. The molecular weight of the 49S subunit is about 1.65 × 10(6), and that of the 28S subunit is 7.8 × 10(5). Both subunits contain about 37% protein and 63% ribonucleic acid. A protein-deficient particle having an s(2̊0.w) value of 15.7S contains about 11% protein and 89% ribonucleic acid. Skin tests showed all subunits and proteins to be active as agents in provoking delayed hypersensitivity, but the 16S protein-deficient particle, as well as the proteins derived from it, was more specific than the subunits themselves.